2021
DOI: 10.1002/adbi.202000199
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Control Over Multicellular Migration Using Green Light Reversible Cell–Cell Interactions

Abstract: cell-cell adhesions leads to the progression of cancer [1c] and subsequent metastasis. [4] Additionally, the control of cell-cell interactions is of interest in the field of bottomup tissue-engineering, which aims to assemble cells as the basic unit into functional tissues. [5] Precise control in time and space over cell-cell interactions is required to successfully assemble appropriate multicellular architectures that resemble the in vivo structures and to control how cells work together within a tissue.In r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…For migration assays in the dark, a long pass filter (514/LP edge basic long pass filter, BLP01-514R-25 from AHF Analysentechnik) was placed in front of the white light source. The wound closure rate was determined with an established script in ImageJ, 25 and the migration angle and correlation length were obtained by using MATLAB version 7.10 (R2020a) with the PIVlab -particle image velocimetry (PIV) application developed by Dr. William Thielicke and Prof. Eize J. Stamhuis (MATLAB script: supplementary data). 48 For spatiotemporal control in the wound-healing assay, the cells were prepared as described earlier, and the experiment was conducted on a confocal microscope (Leica SP8) at 37 °C under 5% CO2.…”
Section: Quantification Of Protein Expression On the Cell Plasma Memb...mentioning
confidence: 99%
See 1 more Smart Citation
“…For migration assays in the dark, a long pass filter (514/LP edge basic long pass filter, BLP01-514R-25 from AHF Analysentechnik) was placed in front of the white light source. The wound closure rate was determined with an established script in ImageJ, 25 and the migration angle and correlation length were obtained by using MATLAB version 7.10 (R2020a) with the PIVlab -particle image velocimetry (PIV) application developed by Dr. William Thielicke and Prof. Eize J. Stamhuis (MATLAB script: supplementary data). 48 For spatiotemporal control in the wound-healing assay, the cells were prepared as described earlier, and the experiment was conducted on a confocal microscope (Leica SP8) at 37 °C under 5% CO2.…”
Section: Quantification Of Protein Expression On the Cell Plasma Memb...mentioning
confidence: 99%
“…[18][19][20] The current state of the art involves an optochemical, 21 and optogenetic tools that allows light-induced dissociation of adherens junctions in through photocleavable linkers, 22 photoswitchable small molecules introduced through metabolic labelling, 23 and artificial photoswitchable surface proteins that mediate artificial cellcell interactions. [24][25][26][27] Yet, these tools are limited by the need for light-responsive chemicals, lack of reversibility, use of UV light or the fact that they do not link to E-cadherin-associated cell signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Nzigou Mombo et al exploited that surface-displayed CarH requires AdoB12 to form a tetramer, and consequently used the AdoB12 concentration in the media (0.5–10 μm) as a tuning knob for the ratio of active CarH. Cells started clustering at concentrations of 1 µm AdoB12 and the area of the clusters increased with the concentration ( Nzigou Mombo et al, 2021 ). Apart from exogenous supplementation, it was shown that de novo engineering of vitamin B12 synthesis in E. coli via an aerobic biosynthetic pathway is possible ( Fang et al, 2018 ).…”
Section: Availability Of Chromophoresmentioning
confidence: 99%
“…[28] CarH is an extremely versatile light-responsive protein, which besides its applications in optogenetics to control receptor activity [29] and gene expression, [30,31] has also been employed to generate light-responsive hydrogels [32] and protein micro-patterning. [33,34] Moreover, when it is expressed as a surface receptor, it is able to mediate light-responsive cell-cell adhesions in mammalian cells, [35] which makes it a suitable candidate to also mediate bacterial cell-cell adhesions.…”
Section: Introductionmentioning
confidence: 99%